Medidas antropométricas e composição corporal em pacientes com colostomia por câncer colorretal: uma investigação prospectiva - Cruz, Amanda Rodrigues (2021)
Introduction: Colorectal cancer (CRC) is one of the most prevalent and incident in the world, with increasing survival rates. Symptoms of the disease, antineoplastic treatments, and adaptation to colostomy (one of the treatments for CRC) can impact by altering body measurements and components. However, studies on this topic are scarce in the literature. Objectives: Evaluate changes in anthropometric and body composition measurements of patients with CRC who underwent recent ostomy surgery and after 3 and 6 months, as well repercussions of antineoplastic treatments in these measurements. Material and methods: A prospective study was carried out with CRC patients with recent colostomy surgery (0-2 months; T0); and 3 months (T1) and 6 months (T2) after T0. Sociodemographic clinical data and antineoplastic treatments were obtained through a structured questionnaire or medical record. Weight, body mass index, body fat, tricipital and subscapular skinfolds, arm circumference, arm muscle circumference and area, and thickness of the adductor pollicis muscle were evaluated in the 3 moments. To understand the changes that occurred on time and the contribution of treatments to these measures Generalized Estimating Equations were analyzed. Results: The study included 41 patients aged between 19 and 82 years old, 53.7% women and 46.3% men. Anthropometric measurements increased in the first three months and decreased from three to six months, except for Body Mass Index, body fat, and arm circumference. Patients who underwent the association of two or more treatments showed decreased measurements when compared to surgery alone. Conclusion: Patients with CRC colostomy showed recovery of anthropometric measurements and their body components in 3 and 6 months after surgery, despite the negative impact of the types of treatment.